Challenges of the new Fiocruz Biodiversity and Health Biobank for preparedness and response to emerging and re-emerging infectious diseases - da Silva, Manuela; Stefanoff, Claudio Gustavo; Eneas, Paula Cristina Rezende; Bôas, Paulo de Carvalho Villas; Nascimento, Carlos Roberto Sobrinho do (Frontiers in Tropical Diseases, 2024)
During the COVID-19 pandemic, the Oswaldo Cruz Foundation (Fiocruz), a Brazilian federal research institution supported by the Brazilian Health Ministry, established a biobank. This biobank began by preserving the SARS-CoV-2 virus and human biological material related to COVID-19. This innovative initiative combined human and biodiversity materials within a single infrastructure. Designed for supporting research, development, and innovation in healthcare and preparedness and response to emerging and re-emerging infectious diseases, the biobank’s focus has since expanded to include various biological materials, leading to its renaming as the Biodiversity and Health Biobank - Fiocruz-BBS (Portuguese: Biobanco da Biodiversidade e Saúde da Fiocruz – BBS-Fiocruz). This paper outlines the challenges of creating and maintaining an adequate infrastructure in a developing country for promoting and supporting scientific research and biotechnological innovation activities in health through processes of depositing, characterizing, preserving, and supplying human and biodiversity biological materials, alongside associated data, while complying with prevailing legal and ethical rules. These processes adhere to stringent quality, biosafety, and biosecurity standards set forth in ISO 20387:2018. Additionally, the challenges of ensuring the Biobank’s long-term sustainability is discussed. This involves a) establishing benchmarks and best practices, b) developing a comprehensive business plan, c) forging partnerships, d) diversifying funding sources, e) ensuring ethical and legal compliance, f) implementing rigorous quality control procedures, and g) investing in human resources and infrastructure. The insights shared in this paper will benefit other biobanks engaged in services related to tropical infectious diseases.